Identification and Partial Characterization of Potential FtsL and FtsQ Homologs of Chlamydia - Ouellette, Scot P.; Rueden, Kelsey J.; AbdelRahman, Yasser M.; Cox, John V.; Belland, Robert J. (Frontiers in Microbiology, 2015)
Chlamydia is amongst the rare bacteria that lack the critical cell division protein FtsZ. By annotation, Chlamydia also lacks several other essential cell division proteins including the FtsLBQ complex that links the early (e.g. FtsZ) and late (e.g. FtsI/Pbp3) components of the division machinery. Here, we report chlamydial FtsL and FtsQ homologs. Ct271 aligned well with E. coli FtsL and shared sequence homology with it, including a predicted leucine-zipper like motif. Based on in silico modeling, we show that Ct764 has structural homology to FtsQ in spite of little sequence similarity. Importantly, ct271/ftsL and ct764/ftsQ are present within all sequenced chlamydial genomes and are expressed during the replicative phase of the chlamydial developmental cycle, two key characteristics for a chlamydial cell division gene. GFP-Ct764 localized to the division septum of dividing transformed chlamydiae, and, importantly, over-expression inhibited chlamydial development. Using a bacterial two-hybrid approach, we show that Ct764 interacted with other components of the chlamydial division apparatus. However, Ct764 was not capable of complementing an E. coli FtsQ depletion strain in spite of its ability to interact with many of the same division proteins as E. coli FtsQ, suggesting that chlamydial FtsQ may function differently. We previously proposed that Chlamydia uses MreB and other rod-shape determining proteins as an alternative system for organizing the division site and its apparatus. Chlamydial FtsL and FtsQ homologs expand the number of identified chlamydial cell division proteins and suggest that Chlamydia has likely kept the late components of the division machinery while substituting the Mre system for the early components.